How to integrate forages in the existing farm system - Gosling, Amanda; Center for International Forestry Research and World Agroforestry (2024)
This poster provides multiple ways for integrating forages in an existing farm system including rotational and relay cropping, under-sowing and intercropping, hedgerow intercropping/alley farming, backyard forage production, strip forage planting, and forage production in degraded areas. The poster forms part of the Climate-Smart Forage and Feed Innovations training package that was co-developed with the Center for International Forestry Research and World Agroforestry (CIFOR-ICRAF) Tanzania and Malawi teams to accelerate the spillover process of validated AICCRA technologies. The poster content is based on knowledge materials sourced from the AICCRA Ethiopia team.